DESAIN SISTEM INFORMASI AKUNTANSI PERUSAHAAN JASA KONSTRUKSI DAN LAPORAN KEUANGAN SESUAI SAK ETAP BAGI PT. INDOYASA MANDIRI PRATAMA - B41111118, Pratiwi Kurniati B41111118 tiwi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
Abstract This research aims to explore information and describe the accounting information system design in the construction company of four cycles that is revenue cycle, expenditure cycle, payroll cycle, and finance cycle, beside that determine the financial statement is made by PT. Indoyasa Mandiri Pratama has standards SAK ETAP. The object of research is PT. Indoyasa Mandiri Pratama Pontianak. Results of this research are PT. Indoyasa Mandiri Pratama need a accounting functions for recording, documentation, and preparing financial statements based SAK ETAP and then two functions performed by one field must be separated as a function of cash and accounting functions, functions reception and storage functions. Keywords : Accounting Information Systems, Construction Services Company, Financial Statements, SAK ETAP